2007
DOI: 10.1074/jbc.m705791200
|View full text |Cite
|
Sign up to set email alerts
|

Aciniform Spidroin, a Constituent of Egg Case Sacs and Wrapping Silk Fibers from the Black Widow Spider Latrodectus hesperus

Abstract: Spiders produce high performance fibers with diverse mechanical properties and biological functions. Molecular and biochemical studies of spider egg case silk have revealed that the main constituent of the large diameter fiber contains the fibroin TuSp1. Here we demonstrate by SDS-PAGE and protein silver staining the presence of a distinct ϳ300-kDa polypeptide that is found in solubilized egg case sacs. Combining matrix-assisted laser desorption ionization tandem time-of-flight mass spectrometry and reverse ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 27 publications
(34 reference statements)
4
65
0
Order By: Relevance
“…Mass Spectrometric Analysis-In-solution tryptic digests of the solubilized wrapping silk as well as other fiber types were performed as previously described (9,10). The MS map and peptide MS/MS spectra were acquired with a MALDI/TOF/ TOF mass spectrometer (4700 Proteomics Analyzer, Applied Biosystems, Foster City, CA) operated in reflector mode or MS/MS mode, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass Spectrometric Analysis-In-solution tryptic digests of the solubilized wrapping silk as well as other fiber types were performed as previously described (9,10). The MS map and peptide MS/MS spectra were acquired with a MALDI/TOF/ TOF mass spectrometer (4700 Proteomics Analyzer, Applied Biosystems, Foster City, CA) operated in reflector mode or MS/MS mode, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Wrapping silk was collected as previously described (10). Prior to imaging, the samples were coated to a thickness of ϳ14 -20 nm with gold alloy using a Pelco SC-7 autosputter coater with an FTM-2 film thickness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 20 years, seven distinct members of the silk gene family have been identified and characterized at the molecular level, which include the silk proteins MaSp1 and MaSp2 (dragline silk) (3)(4)(5), AcSp1 or AcSp1-like (wrapping silk and egg case silk) (6,7), TuSp1 (egg case silk)(8 -11), MiSp1 and MiSp2 or MiSp1-like (temporary spiral capture silk or web reinforcement silk) (12,13), and Flag silk (capture spiral silk in orb weavers) (14). These spider fibroins have revealed that they share a number of distinctive properties, including four fundamental amino acid repeat motifs that characterize the majority of the family: (i) alternating glycine alanine couplets (GA n ), (ii) polyalanine blocks (A n ), (iii) GGX (X ϭ subset of residues, which include Leu, Ile, and Ala), and (iv) GPGX n .…”
mentioning
confidence: 99%
“…In addition to aciniform silks being constituents of egg cases, these fibers are also used for prey capture (Hayashi et al, 2004;Vasanthavada et al, 2007). Because detailed molecular data are available for dragline and tubuliform silks and these fiber types are available in large quantities, we are attempting to study the mechanical behavior of synthetic composite spider silk threads spun from regenerated dragline and egg sac silk protein mixtures.…”
Section: Egg Sac Silksmentioning
confidence: 99%